Effect Of Consumerism Towards Customer Attitudinal Behaviour In Food Industry In Malaysia - Panni, Mohammad Fateh Ali Khan (2006)
The present study will investigate the consumers' perception towards the consumerism issues both in terms of micro issues (fairness on trade practices) and macro issue (environmental consumerism practice) as suggested by Kaynak(1985); and Quazi (2002) as well as the effect of these issues on their ethical attitudinal behaviour.